2021
DOI: 10.1002/pon.5591
|View full text |Cite
|
Sign up to set email alerts
|

Depression in cancer: quality assessment of online patient education resources

Abstract: Objective Psychiatric comorbidities are common among cancer patients. However, little is known about the quality of online information regarding these conditions. This study uses a validated tool to systematically determine the strengths and limitations of websites addressing depression in cancer patients. Methods The term “depression in cancer patients” was searched online using the search engines Google, Yippy, and Dogpile. A set of predetermined inclusion/exclusion criteria was applied to all search results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For those who can access the internet, the content may be inaccurate, misleading, or a source of confusion and distress [ 17 , 29 , 30 ]. A recent review of web-based content from 48 websites for patients with cancer about depression used a validated tool to evaluate the quality of the content [ 31 ]. This review identified issues with accountability in 63% of the websites and readability in 54% and found that only 38% of the websites had been updated in the last 2 years, raising concerns about content accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…For those who can access the internet, the content may be inaccurate, misleading, or a source of confusion and distress [ 17 , 29 , 30 ]. A recent review of web-based content from 48 websites for patients with cancer about depression used a validated tool to evaluate the quality of the content [ 31 ]. This review identified issues with accountability in 63% of the websites and readability in 54% and found that only 38% of the websites had been updated in the last 2 years, raising concerns about content accuracy.…”
Section: Introductionmentioning
confidence: 99%